Method of Determining the Sound Absorbing Coefficient of Materials within the Frequency Range of 5 000–50 000 Hz in a Test Chamber of a Volume of about 2 m3 - Witold MIKULSKI (Archives of Acoustics)
Sound absorption coefficient is a commonly used parameter to characterize the acoustic properties of sound absorbing materials. It is defined within the frequency range of 100–5 000 Hz. In the industrial conditions, many appliances radiating acoustic energy of the frequency range of above 5000 Hz are used and at the same time it is known that a noise within the frequency range of 5 000–50 000 Hz can have a harmful effect on people, hence there is a need to define the coefficient in this frequency range. The article presents a proposal for a method of measurement of the sound absorption coefficient of materials in the frequency range from 5 000 Hz to 50 000 Hz. This method is a modification of the reverberation method with the use of interrupted noise.